SINERGI KEAGAMAAN, SOSIAL, DAN EKONOMI UNTUK MENINGKATKAN KESEJAHTERAAN MASYARAKAT DESA SUKANDEBI - Islah, Putri Tahniah; Oktrigana Wirian (STAI Nusantara Kota Banda Aceh, 2025)
The Community Service Program (KKN) titled “Religious, Social, and Economic Synergy to Improve the Welfare of Sukandebi Village Community” was carried out to address low religious participation, weak social solidarity, and limited economic activities among residents. Ten KKN students implemented the program through a participatory approach that directly involved the community. The activities focused on three main areas: enhancing religious literacy and training young prayer leaders, strengthening social solidarity through community service and youth development, and promoting local economic growth through training in agricultural product processing and micro-enterprise development. Evaluation was conducted through field observations, interviews, and group discussions to assess program effectiveness. The results showed increased enthusiasm for religious activities, the formation of productive social groups, and the emergence of new home-based businesses. The synergy among religious, social, and economic aspects effectively fostered self-reliance and improved the welfare of Sukandebi Village residents